Endoscopic ultrasound-guided transmural gallbladder drainage in malignant obstruction using a novel lumen-apposing stent: a case series (with video) - Chang, Jonathan I.; Dong, Elizabeth; Kwok, Karl K. (Endoscopy International Open, 2019)
Background and aims Current endoscopic methods of biliary decompression in malignant pancreatic neoplasms are often limited by anatomical and technical challenges. In this case series, we report our experience with endoscopic ultrasound (EUS)-guided placement of an electrocautery-enhanced, lumen-apposing self-expandable metallic stent (LAMS) via transmural gallbladder drainage.Methods This is a retrospective case series of nine patients (five male, mean age 63.1 years) who underwent EUS-guided LAMS placement for malignant, obstructive jaundice in the pancreatic head. All nine cases were performed by an experienced interventional endoscopist at a single, tertiary medical center. We review the technical and clinical success rates as well as the incidence of procedural adverse events across the nine patients.Results LAMS placement was technically successful in all cases and there were no procedural adverse events. Seven of nine (77.78 %) patients showed clinical and laboratory improvement immediately following the procedure. One case required re-intervention with interventional radiology guided biliary drain placement. The mean fluoroscopy time was 1.02 minutes.Conclusions EUS-guided LAMS placement for transmural gallbladder drainage in malignant obstruction appears to be a safe and effective technique, allowing patients to proceed to surgery, chemotherapy, or hospice care.